Serum levels of interleukin-17, -18, -22, and -25 in patients with bullous pemphigoid before and after treatment - Xinyi Hong; Xinyi Hong; Xinyi Hong; Xinyi Hong; Xiuqin Wang; Xiuqin Wang; Xiuqin Wang; Xiuqin Wang; Yin Cheng; Yin Cheng; Yin Cheng; Yin Cheng; et al. (Frontiers in Medicine)
ObjectiveThis study aimed to explore the relationship between serum levels of interleukin-17 (IL-17), interleukin-18 (IL-18), interleukin-22 (IL-22), interleukin-25 (IL-25), anti-BP180 antibodies, anti-BP230 antibodies, and immunoglobulin E (IgE) and the percentage of eosinophils (EOS) in peripheral blood and disease activity and severity in bullous pemphigoid (BP) patients.MethodsBlood samples from 61 BP inpatients were collected on the first day of admission and again 1 week after systemic corticosteroid treatment. Additionally, blood specimens were collected from 61 healthy controls. The concentrations of IL-17, IL-18, IL-22, IL-25, IgE, and anti-BP180 or anti-BP230 antibodies were measured using ELISA kits. Various statistical methods were used, including the Wilcoxon test, multifactorial logistic regression, ROC survival curve, and Spearman’s correlation analysis.ResultsThe mean serum levels of IL-17, IL-18, IL-22, IL-25, and EOS percentage in BP patients were higher than those in healthy controls (all p < 0.001), and all of these levels decreased after treatment (all p < 0.001). There was no statistically significant difference in the titer of anti-BP180 or anti-BP230 antibodies before and after treatment. A binary multivariate logistic regression analysis indicated the statistically significant effect of IL-18, IL-25, or EOS on BP (p < 0.001). Spearman’s correlation analysis revealed that the serum levels of IL-17, IL-22, or IL-25 were all strongly correlated with the involved surface area (p < 0.001). In addition, the serum level of IL-17 and the percentage of EOS were associated with the titer of anti-BP180 antibodies (p < 0.05).ConclusionIL-17, IL-18, IL-22, IL-25, or EOS may be involved in the development of BP, and can be used as biological indicators for monitoring disease severity.